2020
DOI: 10.3390/ijms21228802
|View full text |Cite
|
Sign up to set email alerts
|

Calciprotein Particles Cause Endothelial Dysfunction under Flow

Abstract: Calciprotein particles (CPPs), which increasingly arise in the circulation during the disorders of mineral homeostasis, represent a double-edged sword protecting the human organism from extraskeletal calcification but potentially causing endothelial dysfunction. Existing models, however, failed to demonstrate the detrimental action of CPPs on endothelial cells (ECs) under flow. Here, we applied a flow culture system, where human arterial ECs were co-incubated with CPPs for 4 h, and a normolipidemic and normote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 46 publications
3
29
1
2
Order By: Relevance
“…To investigate the mechanism of the above-mentioned associations, we complemented the balloon angioplasty of rat abdominal aorta with daily intravenous injections of CPPs, a newly discovered trigger of endothelial dysfunction [ 42 , 43 , 44 ], for 5 days. Control rats were subjected to balloon injury alone.…”
Section: Resultsmentioning
confidence: 99%
“…To investigate the mechanism of the above-mentioned associations, we complemented the balloon angioplasty of rat abdominal aorta with daily intravenous injections of CPPs, a newly discovered trigger of endothelial dysfunction [ 42 , 43 , 44 ], for 5 days. Control rats were subjected to balloon injury alone.…”
Section: Resultsmentioning
confidence: 99%
“…Vascular calci cation, including CAC, is strongly driven by in ammation (31,32). Calcifying nanoparticles are thought to play a causal role in vascular calci cation, potentially by promoting endothelial dysfunction and downregulation of atheroprotective transcription factors among others (33,34). Higher IgG levels directed against calcifying nanoparticles were demonstrated in Turkish individuals with CAC and these IgG levels correlated positively with CAC score (33).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent experiments showed that a 4-h incubation of primary coronary artery and internal thoracic artery endothelial cells with calciprotein particles causes adhesion of leukocytes to arterial endothelial cells under flow accompanied by an increase in VCAM1 and ICAM1 [ 82 – 84 ]. Both complete and vesicle-free conditioned medium from CPP-treated primary coronary artery endothelial cells led to an increased expression of VCAM1, ICAM1, SELE and SELP genes in combination with an elevated expression of IL6, CXCL8, CCL2, CXCL1 and MIF genes, increased expression of VCAM1 and ICAM1 receptors, and augmented release of IL-6, IL-8 and MCP-1/CCL2 when added to intact human coronary artery endothelial cells.…”
Section: Mechanisms Of Endothelial Dysfunctionmentioning
confidence: 99%